MENCARI BENTUK PEREKONOMIAN ISLAM - M.Si, Gampito (Faculty of Shariah of State Institute for Islamic Studies Batusangkar, Indonesia, 2011)
World’s economic condition suffers from imbalance. Great gaps among countries take place which in turn violate justice and balance in terms of economic asset ownership. Studies on Islamic economy should get more attention and chances in universities Curriculum for Islamic Economy studies should be frequently and continuously revised by combining Islamic normative and empirical quantitative approaches. It should be noted that during its golden age, the Islamic scholars have give significant contribution toward the science of economy. Those scholars have written, searched and yielded economic theories which remain relevant to be studied and implemented up to present.